Cross-sectional study investigating the prevalence and causes of vision impairment in Northwest Portugal using capture-recapture - Ramos, Pedro Lima (2022)
Objectives The aim of this study was to estimate the prevalence and causes of vision impairment (VI) in Portugal.Setting Information about people with VI was obtained from primary care centres, blind association (ACAPO) and from hospitals (the PCVIP study) in the Northwest of Portugal during a period spanning years 2014-2015. Causes of VI were obtained from hospitals.Participants Administrative and medical records of people with visual acuity in the better seeing eye of 0.5 decimal (0.30logMAR) or worse and/or visual field less than 20 degrees were investigated. Capture-recapture with log-linear models was applied to estimate the number of individuals missing from lists of cases obtained from available sources.Primary and secondary outcome measures Log-linear models were used to estimate the crude prevalence and the category specific prevalence of VI.Results Crude prevalence of VI was 1.97% (95% CI 1.56% to 2.54%), and standardised prevalence was 1% (95% CI 0.78% to 1.27%). The age-specific prevalence was 3.27% (95% CI 2.36% to 4.90%), older than 64 years, 0.64% (95% CI 0.49% to 0.88%), aged 25-64 years, and 0.07% (95% CI 0.045% to 0.13%), aged less than 25 years. The female-to-male ratio was 1.3, that is, higher prevalence among females. The five leading causes of VI were diabetic retinopathy, cataract, age-related macular degeneration, glaucoma and disorders of the globe.Conclusions The prevalence of VI in Portugal was within the expected range and in line with other European countries. A significant number of cases of VI might be due to preventable cases and, therefore, a reduction of the prevalence of VI in Portugal seems possible. Women and old people were more likely to have VI and, therefore, these groups require extra attention. Future studies are necessary to characterise temporal changes in prevalence of VI in Portugal.